Pengaruh Dana Alokasi Umum (DAU) dan Pendapatan Asli Daerah (PAD) terhadap Belanja Daerah di Provinsi Kalimantan Barat - Rusmita, Sari (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2016)
The local government can take over their support of various factors resources that can drive the wheels of government organizations in order to achieve objectives. Local Government Expenditure is expected to meet the needs of terrain is through the PAD, as well as other sources of revenue. This study uses secondary data obtained from the Central Statistics Agency of West Kalimantan Year 2009-2014, namely in the form of DAU, PAD, and Expenditure in West Kalimantan. The results showed that the F test between DAU and PAD together a significant influence on regional spending is shown on the F count (3,598) F table (3.032), at a significance level of 0.033 under significance level 0,05 (0.033 0.05).